The efficacy and safety of ethyl methyl hydroxypyridine succinate used as part of sequential therapy in patients with chronic cerebral ischemia - V. V. Burdakov; D. V. Krasnykh (Неврология, нейропсихиатрия, психосоматика, 2020)
Objective: to investigate the efficacy and safety of Mexidol® FORTE 250 in patients with chronic cerebral ischemia (CCI) in the presence of hypertension and atherosclerosis.Patients and methods. The investigation enrolled 20 patients aged 45 to 75 years with CCI in the presence of hypertension and atherosclerosis, who received intravenous Mexidol® administered dropwise at a dose of 500 mg once a day for 14 days, followed by oral Mexidol® FORTE 250 mg thrice a day for 60 days (a study group). A control group consisted of 14 patients with CCI in the presence of hypertension concurrent with atherosclerosis, who were prescribed combination therapy for CCI without using these drugs. The patients were examined before and at 14 and 60 days of treatment. The investigators studied subjective complaints, neurological symptoms, and the indicators of the Tinetti Performance-Oriented Mobility Assessment in Elderly Patients; the Montreal Cognitive Assessment (MoCA); the Hamilton Anxiety Rating Scale (HARS); asthenia rating scales (Multidimensional Fatigue Inventory, MFI-20); and the Clinical Global Impression (CGI) scale over time.Results and discussion. Therapy with Mexidol® in patients with CCI in the presence of hypertension and atherosclerosis was found to be accompanied by positive changes in the asthenia rating scale MFI-20, cognitive functions assessed by MoCA, as well as Tinetti movement coordination. No significant differences in these indicators were noted in patients of the control group. Combination treatment for CCI with Mexidol®and Mexidol® FORTE 250 as a sequential therapy was twice more effective than that without using these drugs, as shown by the scales as a whole and it was up to 10 times greater for individual scale parameters. Conclusion. The study of Mexidol® FORTE 250 as part of the sequential therapy, which was used according to the above regimen, indicates its clinical efficacy and safety in patients with CCI.